PSXI-27 Excretion of purine derivatives and rumen microbial protein synthesis in buffaloes fed sugarcane. (7th December 2018) - Pessoa, R; do Carmo, M; Alves, L; Costa, C; Pereira, K; Neves, M; Melo, S; Bartolomeu, C; Ribeiro, L
Abstract: The objective was to determine effects of sugarcane association and concentrate on excretion of purine derivatives and rumen microbial protein synthesis in Murrah buffaloes. Four uncastrated male animals with an average initial body weight of 300.0 ± 15.6 kg and fitted with cannulas in the rumen were assigned to a 4 × 4 latin square design, with four treatments and four experimental periods. The animals were kept in indoor facilities with individual stalls provided with a feeder and drinker. Experimental diets consisted of the sugarcane (Saccharum officinarum L.) associated to concentrate (corn, wheat bran, soybean meal, urea and mineral) in the proportions of 20, 40, 60 and 80%. The diets were adjusted to contain 13.5% of crude protein and were supplied ad libitum, as a complete ration, twice daily, at 08.00 and 16.00 h, formulated to provide 10% as orts. The sugarcane was corrected with urea and ammonium sulfate. Each experimental period lasted 17 days, with the first thirteen days dedicated to animal adaptation. The data were analyzed using the PROC GLM and PROC REG procedure of SAS. The excretion of allantoin and uric acid presented a linear effect (P < 0.05), which increased by 0.20 and 0.30 mmol/day, respectively, for every 1% level of concentrate in the diet. The microbial protein synthesis was positively affected (P < 0.05) by concentrate levels, which increased 2.3 g of microbial crude protein/day for every 1% level of concentrate in the diet. Data suggest that levels up to 80% of concentrate result in greater microbial protein synthesis by buffaloes fed sugarcane diets.